Information sharing in self-directed work groups in a competitive environment. - Jackson, Bronwyn (My University, 2012)
Self-directed work groups are a growing phenomenon in the field of organisational psychology (Kauffeld, 2006; Neck & Manz, 1994). While much is known about what factors affect information sharing in these kinds of groups, little is known about why these factors have an impact and how they relate to each other. Through the concept of hidden profiles (tasks that by nature have shared and unshared information), this study explored the information sharing and group decision making processes and aimed to illuminate the group processes involved. The study employed a qualitative, ideographic approach where case studies were used. The sample consisted of twenty four undergraduate and postgraduate students studying at the University of the Witwatersrand divided into groups of four members each. A group task to rank the best candidate for a job was self-designed based on the theory and design utilized by Stasser and Titus (1985; 1987). This was first completed individually and then as a group – the group discussion was filmed and coded using a self-developed observation rubric. Participants also completed a self-developed post-task questionnaire regarding their perspectives of various aspects of the decision making process. The analysis was carried out using frequency counts and thematic content analysis. It was found that all the groups discussed more shared information and more unshared negative information was discussed than unshared positive information. Information sharing increased when there was debate about which pieces of information were relevant. In most cases, group members were motivated to share information because they wanted to have their opinion heard. Although the majority of the sample stated that they did not withhold any information, there was evidence of strategic information sharing. Group 5 made a decision that was closest to the ideal decision. Characteristics of this group that could have contributed to this included: long duration of discussion; high number of talking turns; respecting each other’s talking turns; moderate levels of disagreement; no obvious role of leader; moderately high levels of group familiarity; diversity in race not gender; similar educational backgrounds and a norm of critical evaluation. The study found that the interactions between factors that were perceived to affect the information sharing and decision-making (such as duration of discussion, number of talking turns, group familiarity, competitive aspects, group composition and group roles) were more interwoven than previously thought.
Keywords: Information sharing; Hidden profile; Competitive environment; Self-directed work groups; Group dynamics; Decision-making